Wunderlich's Syndrome due to ruptured renal Angiomyolipoma - Che Alhadi, Shahidah; Che' Man, Mohamad; Syed Mohsin, Syed Hasanul Hadi; Wan Mokhter, Wan Mokhzani; Gohar Rahman, Mohd Nor (Science Forecast Publication, 2019)
Wunderlich’s syndrome or spontaneous renal hematoma is rare condition but can be life threatening. Renal tumours are the most common etiology. CT plays a vital role in identifying the perirenal hematoma and diagnosing the underlying cause. Selective arterial embolization is the current treatment of choice in ruptured renal angiomyolipoma, especially in life threatening cases.